Hak dan tanggungjawab Akta Universiti dan Kolej Universiti - Rohani Abd. Rahim; Anisah Che Ngah; Kamal Halili Hassan; Aishah Hj. Bidin; Raja Rohana Raja Mamat (Penerbit Universiti Kebangsaan Malaysia, 1992)
Rights and responsibilities of college and university in Malaysia according to the University and College Act, 1971.